The prognostic utility of the ratio of lymphocyte to monocyte in patients with metastatic colorectal cancer: a systematic review and meta-analysis - Mei, Pingping; Huang, Li; Lin, Lu; Chen, Yan; Guo, Xiutian (Frontiers in Oncology, 2025)
BackgroundAlthough advancements in treatment have resulted in improved overall outcomes for patients diagnosed with colorectal cancer, the prognosis remains unfavorable for individuals with metastatic colorectal cancer (mCRC). The association between lymphocyte/monocyte ratio (LMR) and clinical outcomes in mCRC patients is a subject of controversy. To systematically evaluate the correlation between LMR and prognostic factors in individuals with mCRC, we conducted this meta-analysis.MethodsThe databases PubMed, Embase, Web of Science, and the Cochrane Library were systematically searched for all relevant studies from their inception until October 26, 2024. Study selection was conducted based on predetermined inclusion and exclusion criteria. The primary outcomes of interest included prognosis measures such as overall survival (OS), progression-free survival (PFS), disease-free survival (DFS), and cancer-specific survival (CSS) in patients with metastatic colorectal cancer. Random-effects models or fixed-effects models were used to determine the pooled risk ratio (HR) and corresponding 95% confidence interval (CI) for each outcome indicator. Additionally, the pooled odds ratio (OR) and its corresponding 95% CI were calculated for LMR and clinicopathological characteristics.ResultsFourteen studies involving 3,089 patients were included in the analysis. The pooled analysis found that high LMR was correlated with better OS (HR: 0.55, 95% CI: 0.49-0.62, p<0.00001), PFS (HR: 0.68, 95% CI: 0.57-0.81, p<0.0001) and CSS(HR: 0.55, 95% CI: 0.32-0.95, p=0.03),The prognostic value of high LMR values for DFS(HR: 0.93, 95% CI: 0.78-1.12, p=0.46) in patients with metastatic rectal cancer was not found to be significant. We performed subgroup analyses based on study characteristics to confirm the robustness of our findings. Further clinicopathological analysis showed no significant difference between patients with elevated LMR and those without elevated LMR.ConclusionsIn conclusion, the results demonstrate a robust correlation between elevated LMR levels and a favorable prognosis in terms of overall survival (OS), progression-free survival (PFS), and cancer-specific survival (CSS) among patients diagnosed with metastatic colorectal cancer. However, further high-quality prospective studies are warranted to validate our findings since the majority of current investigations have relied on retrospective study designs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024496467, identifier CRD42024496467.